Facilitators of and barriers to healthcare providers’ adoption of harm reduction in cannabis use: a scoping review protocol - Christian Dagenais; Jean-Sébastien Fallu; Roula Haddad; Christophe Huynh (BMJ Open, 2024)
Introduction The high prevalence of cannabis use and the potential for negative effects indicate the need for effective prevention strategies and treatment of people who use cannabis. Studies show that harm reduction (HR) in cannabis use is effective in minimising the harmful consequences of the substance. However, health professionals often misunderstand it and resist its adoption due to various obstacles. To our knowledge, there has been no review of the scientific literature on the factors that facilitate or hinder practitioners’ adoption of HR in cannabis use. To fill this gap, we aim to identify, through a scoping review, facilitators and barriers to healthcare providers’ adoption of HR in cannabis use in Organisation for Economic Cooperation and Development (OECD) countries.Methods and analysis Our methodology will be guided by the six-step model initially proposed by Arksey and O’Malley (2005). The search strategy will be executed on different databases (Medline, PsycINFO, CINAHL, Web of Science, Embase, Sociological Abstracts, Érudit, BASE, Google Web and Google Scholar) and will cover articles published between 1990 and October 2022. Empirical studies published in French or English in an OECD country and identifying factors that facilitate or hinder healthcare providers’ adoption of HR in cannabis use, will be included. Reference lists of the selected articles as well as relevant systematic reviews will be scanned to identify any missed publications by the electronic searches.Ethics and dissemination Ethics approval is not required. The results will be disseminated through various activities (eg, publication in peer-reviewed journals, conferences, webinars and knowledge translation activities). The results will also allow us to conduct a future study aiming to develop and implement a knowledge translation process among healthcare practitioners working with youth in Quebec in order to enhance their adoption of HR in cannabis use.